Common and Specific Factors Approaches to Home-Based Treatment: I-FAST and MST. (July 2013) - Lee, Mo Yee; Greene, Gilbert J.; Fraser, J. Scott; Edwards, Shivani G.; Grove, David; Solovey, Andrew D.; Scott, Pamela
Objectives: This study examined the treatment outcomes of integrated families and systems treatment (I-FAST), a moderated common factors approach, in reference to multisystemic therapy (MST), an established specific factor approach, for treating at-risk children and adolescents and their families in an intensive community-based setting. Method: This study used a nonrandomized noninferiority trial design to compare the outcomes of 79 families who received I-FAST, the test intervention, to 47 families who have received MST, the reference intervention. Results: I-FAST was noninferior to MST in reducing problem severity and improving functioning based on youth, parents, and workers' assessments. Conclusions: While the nonrandomized design of this study precludes any definitive conclusions, implications of the study were discussed with respect to the debate regarding common factors and specific factor approaches to family treatment and implementation of evidence-based treatments.